Colonic electrical stimulation promotes colonic motility through regeneration of myenteric plexus neurons in slow transit constipation beagles. Issue 5 (17th May 2019) - Wang, Yongbin; Wang, Qian; Kuerban, Kudelaidi; Dong, Mengxue; Qi, Feilong; Li, Gang; Ling, Jie; Qiu, Wei; Zhang, Wenzhong; Ye, Li
Abstract : Slow transit constipation (STC) is a common disease characterized by markedly delayed colonic transit time as a result of colonic motility dysfunction. It is well established that STC is mostly caused by disorders of relevant nerves, especially the enteric nervous system (ENS). Colonic electrical stimulation (CES) has been regarded as a valuable alternative for the treatment of STC. However, little report focuses on the underlying nervous mechanism to normalize the delayed colonic emptying and relieve symptoms. In the present study, the therapeutic effect and the influence on ENS triggered by CES were investigated in STC beagles. The STC beagle model was established by oral administration of diphenoxylate/atropine and alosetron. Histopathology, electron microscopy, immunohistochemistry, Western blot analysis and immunofluorescence were used to evaluate the influence of pulse train CES on myenteric plexus neurons. After 5 weeks of treatment, CES could enhance the colonic electromyogram (EMG) signal to promote colonic motility, thereby improving the colonic content emptying of STC beagles. HE staining and transmission electron microscopy confirmed that CES could regenerate ganglia and synaptic vesicles in the myenteric plexus. Immunohistochemical staining showed that synaptophysin (SYP), protein gene product 9.5 (PGP9.5), cathepsin D (CAD) and S-100B in the colonic intramuscular layer were up-regulated by CES. Western blot analysis and immunofluorescence further proved that CES induced the protein expression of SYP and PGP9.5. Taken together, pulse train CES could induce the regeneration of myenteric plexus neurons, thereby promoting the colonic motility in STC beagles.